Synthesis and crystal structures of dialkyl[1, 1-bis(alkylchloroalanyl)organylmethyl]phosphinedialkylchloroalane(1/1) complexes. Issue 13 (3rd July 2017) - Bani-Fwaz, Mutasem Z.; Fazary, Ahmed E.; Becker, Gerd
Abstract: Dialkyl[1, 1-bis(alkylchloroalanyl)organylmethyl]phosphinedialkylchloroalane(1/1) complexes (1a –1d ) were synthesized and fully characterized. In1a –1d, dative bonding between phosphorus or chlorine as a donor atom and aluminum as an acceptor atom results in a bicyclic system. The 31 P 1 H NMR spectra of all compounds dissolved in d6 -benzene indicate the presence of several isomers in solution. The 27 Al 1 H NMR spectra of1a –1d dissolved in d6 -benzene as well show very broad singlets between 177 and 140 ppm. For all compounds, crystal structures consist of two fused four- and five-membered rings. The 1λ 3 -phosphaalkyne reacts at the Al–C bond of the starting material, whereas the Al–Cl moiety remains intact. The heterocycle isolated is a molecular complex of the underlying insertion compound and a third equivalent of dialkylaluminum chloride. The four- and five-membered rings both contain two chlorine-bridged aluminum atoms, Al3 and Al1, slightly more symmetrical than that between Al1 and Al6. In the four-membered ring the two aluminum atoms Al1 and Al6 approach each other at an average distance of 289.1 pm which tallies with the element–element distance (286.3 pm) in aluminum metal. Abstract :